(untitled) (International Journal of Natural Sciences, 2016)
This study was carried out to evaluate the effects of supplementation of commercial layer feed on body weight, egg production and haematological profile of the laying ducks rearing under the rural condition of Bangladesh. Twenty indigenous ducks (Khaki Campbell x Local duck) of 24 weeks old was selected from a farm and randomly divided into four equal groups (n=5) and numbered as group T0, T1, T2 & T3. The different amount of feed was supplied into four groups for three months. The all four groups (T0, T1, T2 and T3) were fed with routine feeding in scavenging condition. But T1 group supplemented with 120 gm, T2 group 60 gm and T3 group 30 gm of commercial feed. Significant differences were found in both egg production and haematological profile of ducks in compared to control group. Egg production was significantly (P<0.01) higher in T1 group compared to other groups. During the study the body weight gain were shown the same pattern being significantly (P<0.05) higher in T1 group compared to T0, T2 and T3 groups. On the other hand, the values of total erythrocyte count (TEC), total leukocyte count (TLC), haemoglobin content (Hb) and packed cell volume (PCV) increased significantly (P<0.05) in the groups of T1 and T2 compared to the control group (T0). But the value of MCV, MCH and MCHC of T1, T2 & T3 groups decreased significantly (P<0.05) than that of the control group. Results of the present study revealed that the amount of supplementation of commercial layer feeds was very important for improving the haematological profile and egg production of ducks. So, the additional commercial layer feed supplementation may be beneficial for duck farming. International Journal of Natural Sciences (2015), 5(1) 35-40